Global sensitivity analysis of KINEROS2 hydrologic model parameters representing green infrastructure using the STAR-VARS framework. (October 2020) - Korgaonkar, Yoganand; Meles, Menberu B.; Guertin, D. Phillip; Goodrich, David C.; Unkrich, Carl
Abstract: The KINematic runoff and EROSion model (version 2; KINEROS2) provides an urban component that is capable of modeling urban hydrology including green infrastructure (GI) practices at various scales. The KINEROS2 model provides 15 parameters that can represent a variety of GI practices. The goal of this study is to understand the sensitivity of the KINEROS2 model outputs (infiltration, peak flow, runoff volume, and outflow hydrograph) to these 15 parameters, across seven different precipitation events, and at the watershed as well as the parcel scale. A global sensitivity analysis (GSA) was performed using the Variogram Analysis of Response Surfaces (VARS) framework to produce sensitivity metrics. Results from the time-aggregate GSA indicate that parameter sensitivities follow trends based on precipitation intensity and duration. Time-varying GSA indicate sensitivity of parameters to hyetograph shape, especially the duration to maximum precipitation intensity. The variation in sensitivity is influenced by the peaks and valleys in the precipitation hyetograph. Highlights: On-parcel retention basin KINEROS2 parameters are most sensitive for high intensity events. On-street green infrastructure parameters are most sensitive for low intensity events. Model response is sensitive to scale, i.e. at watershed scale versus single parcel. Precipitation intensity and hyetograph shape influence parameter sensitivity.